Chora, Intervals in the philosophy of architecture - Pérez Gómez, Alberto, 1949-; Parcell, Stephen, 1954- (Chora ;, 1996)
In this second volume in the Chora series, contributing authors take an interdisciplinary approach to architecture and other cultural concerns, challenging readers to consider alternatives to conventional aesthetic and technological reductions.